Volume 7: 28th International Conference on Design Theory and Methodology 2016
DOI: 10.1115/detc2016-60407
|View full text |Cite
|
Sign up to set email alerts
|

The Design for Additive Manufacturing Worksheet

Abstract: Additive manufacturing (AM) technologies have become integral to the modern manufacturing process. These roles are filled both in prototyping and production. Many studies have been conducted and lists been written on guidelines for AM. While these lists are useful, virtually none are written in a way that is accessible to novice users of AM, such as Makers. Most guidelines assume the user has extensive prior knowledge of the process, apply to only a few AM technologies, or describe benefits of the technology t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 50 publications
0
45
0
5
Order By: Relevance
“…As Rias' proposal underlines, during the search for ideas stage, there are insufficient product data to analyse the product's manufacturability, so experts may have to be called into analyse its potential [30]. Ideas can be evaluated with adapted tools, like those developed by Booth [31], taking the form of a matrix where design rules are graphically formulated to evaluate the AM potential.…”
Section: Additive Manufacturing Performancementioning
confidence: 99%
See 1 more Smart Citation
“…As Rias' proposal underlines, during the search for ideas stage, there are insufficient product data to analyse the product's manufacturability, so experts may have to be called into analyse its potential [30]. Ideas can be evaluated with adapted tools, like those developed by Booth [31], taking the form of a matrix where design rules are graphically formulated to evaluate the AM potential.…”
Section: Additive Manufacturing Performancementioning
confidence: 99%
“…• t 2 = F, total lifecycle considerations [20]. • t 3 = IV, DFAM worksheet [31]. • t 4 = α , eco-ideation [23]…”
Section: Tool Selectionmentioning
confidence: 99%
“…Previous research has developed checklists, rule-based catalogs, and worksheets for integrating design for AM (DfAM) considerations into the design process [5,26]. Such tools usually provide broad guidelines and span across multiple AM techniques.…”
Section: Design For Rapid Prototypingmentioning
confidence: 99%
“…However, previous studies have reported that students tend to rush to fabrication without accounting for design flaws or performing model checks [4]. They also ignore considerations for support structures and expect AM parts to have similar endurance to machined parts [5], and find it difficult to learn from mistakes made as they seldom reflect on their errors [6]. Learning aids such as worksheets [5] and expert-supervision during fabrication have been successful in remedying some of these concerns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation